Symbol

# Calculator search results

Formula
Number of solution
Relationship between roots and coefficients
Graph
$y = 3 x ^ { 2 } - 5 x + 3$
$y = 0$
$y$Intercept
$\left ( 0 , 3 \right )$
Minimum
$\left ( \dfrac { 5 } { 6 } , \dfrac { 11 } { 12 } \right )$
Standard form
$y = 3 \left ( x - \dfrac { 5 } { 6 } \right ) ^ { 2 } + \dfrac { 11 } { 12 }$
$3x ^{ 2 } -5x+3 = 0$
$\begin{array} {l} x = \dfrac { 5 + \sqrt{ 11 } i } { 6 } \\ x = \dfrac { 5 - \sqrt{ 11 } i } { 6 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 3 } } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 3 } } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - \dfrac { 5 } { 6 } \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
 Move the constant to the right side and change the sign 
$\left ( x - \dfrac { 5 } { 6 } \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x - \dfrac { 5 } { 6 } \right ) ^ { 2 } = - 1 + \left ( \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } }$
 When raising a fraction to the power, raise the numerator and denominator each to the power 
$\left ( x - \dfrac { 5 } { 6 } \right ) ^ { 2 } = - 1 + \dfrac { \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 6 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 ^ { 2 } } { 6 ^ { 2 } } }$
 Organize the expression 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 36 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 6 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 36 } }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 6 } } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 36 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 6 } } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 11 } { 36 } } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { \sqrt{ 11 } i } { 6 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 6 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { \sqrt{ 11 } i } { 6 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 6 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { \sqrt{ 11 } i } { 6 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { \sqrt{ 11 } i } { 6 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { \sqrt{ 11 } i } { 6 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { \sqrt{ 11 } i } { 6 } } \end{array}$
 Organize the expression 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 + \sqrt{ 11 } i } { 6 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 - \sqrt{ 11 } i } { 6 } } \end{array}$
$\begin{array} {l} x = \dfrac { 5 + \sqrt{ 11 } i } { 6 } \\ x = \dfrac { 5 - \sqrt{ 11 } i } { 6 } \end{array}$
Calculate using the quodratic formula$($Imaginary root solution$)$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } $Solve the quadratic equation$ ax^{2}+bx+c=0 $using the quadratic formula$ \dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - \left ( - 5 \right ) \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 } }x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 5 \right ) \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 } $Simplify Minus$ x = \dfrac { 5 \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 3 } } { 2 \times 3 } $Remove negative signs because negative numbers raised to even powers are positive$ x = \dfrac { 5 \pm \sqrt{ 5 ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 3 } } { 2 \times 3 } $Calculate power$ x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 25 } - 4 \times 3 \times 3 } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ 25 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } } } { 2 \times 3 } $Multiply the numbers$ x = \dfrac { 5 \pm \sqrt{ 25 \color{#FF6800}{ - } \color{#FF6800}{ 36 } } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 25 } \color{#FF6800}{ - } \color{#FF6800}{ 36 } } } { 2 \times 3 } $Subtract$ 36 $from$ 25x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 11 } } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ - 11 } } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } } $Multiply$ 2 $and$ 3x = \dfrac { 5 \pm \sqrt{ - 11 } } { \color{#FF6800}{ 6 } }x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ - } 11 } } { 6 } $Subtracting (-) from the square root gives i$ x = \dfrac { 5 \pm \sqrt{ 11 } \color{#FF6800}{ i } } { 6 }\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 \pm \sqrt{ 11 } i } { 6 } } $Separate the answer$ \begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 + \sqrt{ 11 } i } { 6 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 - \sqrt{ 11 } i } { 6 } } \end{array} $Do not have the solution$ $Calculate using the quadratic formula$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 5 \right ) \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 } $Simplify Minus$ x = \dfrac { 5 \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 3 } } { 2 \times 3 } $Remove negative signs because negative numbers raised to even powers are positive$ x = \dfrac { 5 \pm \sqrt{ 5 ^ { 2 } - 4 \times 3 \times 3 } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 3 } } { 2 \times 3 } $Calculate power$ x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 25 } - 4 \times 3 \times 3 } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ 25 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } } } { 2 \times 3 } $Multiply the numbers$ x = \dfrac { 5 \pm \sqrt{ 25 \color{#FF6800}{ - } \color{#FF6800}{ 36 } } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 25 } \color{#FF6800}{ - } \color{#FF6800}{ 36 } } } { 2 \times 3 } $Subtract$ 36 $from$ 25x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 11 } } } { 2 \times 3 }x = \dfrac { 5 \pm \sqrt{ - 11 } } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } } $Multiply$ 2 $and$ 3x = \dfrac { 5 \pm \sqrt{ - 11 } } { \color{#FF6800}{ 6 } }\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 \pm \sqrt{ - 11 } } { 6 } } $The square root of a negative number does not exist within the set of real numbers$  $Do not have the solution$  $Do not have the real root$ $Find the number of solutions$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } $Determine the number of roots using discriminant,$ D=b^{2}-4ac $from quadratic equation,$ ax^{2}+bx+c=0\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 }D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 3 $Remove negative signs because negative numbers raised to even powers are positive$ D = 5 ^ { 2 } - 4 \times 3 \times 3D = \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } - 4 \times 3 \times 3 $Calculate power$ D = \color{#FF6800}{ 25 } - 4 \times 3 \times 3D = 25 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } $Multiply the numbers$ D = 25 \color{#FF6800}{ - } \color{#FF6800}{ 36 }D = \color{#FF6800}{ 25 } \color{#FF6800}{ - } \color{#FF6800}{ 36 } $Subtract$ 36 $from$ 25D = \color{#FF6800}{ - } \color{#FF6800}{ 11 }\color{#FF6800}{ D } = \color{#FF6800}{ - } \color{#FF6800}{ 11 } $Since$ D<0 $, there is no real root of the following quadratic equation$  $Do not have the real root$ \alpha + \beta = \dfrac { 5 } { 3 } , \alpha \beta = 1$Find the sum and product of the two roots of the quadratic equation$\color{#FF6800}{ 3 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } $In the quadratic equation$ ax^{2}+bx+c=0 $, if the two roots are$ \alpha, \beta $, then it is$ \alpha + \beta =-\dfrac{b}{a} $,$ \alpha\times\beta=\dfrac{c}{a}\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 5 } { 3 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 3 } { 3 } }\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 5 } { 3 } } , \alpha \beta = \dfrac { 3 } { 3 } $Solve the sign of a fraction with a negative sign$ \alpha + \beta = \color{#FF6800}{ \dfrac { 5 } { 3 } } , \alpha \beta = \dfrac { 3 } { 3 }\alpha + \beta = \dfrac { 5 } { 3 } , \alpha \beta = \color{#FF6800}{ \dfrac { 3 } { 3 } } $Reduce the fraction$ \alpha + \beta = \dfrac { 5 } { 3 } , \alpha \beta = \color{#FF6800}{ 1 }\$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture